Towards sustainable landscapes guidelines for regulating aesthetics and environmental quality of the landscapes - Porciuncula-Alfonso, Maria Mynn (Quezon City College of Architecture, University of the Philippines Diliman, 2003)
The study analyzes the six major elements of a town utilizing concepts of sustainable development with special emphasis on landscapes, as follows: scenic, natural and historic sites; roads and streets; parks and plazas; dump sites; and plants and trees. It identifies the problems relating to environment and landscape focusing in the town proper of Tanay, Rizal. Guidelines and design standards for each topic shall be outlined and presented through graphics and photographs. A handbook especially written for the Barangay (smallest local government unit) will culminate this thesis. It is concentrated on concepts of visual analysis, regenerative designs and landscape development.
Thesis (Master of Tropical Landscape Architecture)--University of the Philippines, Diliman.
Keywords: Landscape assessment -- Philippines -- Tanay (Rizal).